Resistive cooling of highly charged ions in a Penning trap to a fluidlike state - Ebrahimi, Mohammad Sadegh; Quint, Wolfgang (Physical review, 2018)
We perform a detailed experimental study of resistive cooling of large ensembles of highly charged ions such as Ar13+ in a cryogenic Penning trap. Different from the measurements reported by Vogel et al. [M. Vogel et al., Phys. Rev. A 90, 043412 (2014)], we observe purely exponential cooling behavior when conditions are chosen to allow collisional thermalization of the ions. We provide evidence that in this situation resistive cooling time constants and final temperatures are independent of the initial ion energy and that the cooling time constant of a thermalized ion ensemble is identical to the single-ion cooling time constant. For sufficiently high ion number densities, our measurements show discontinuities in the spectra of motional resonances which indicate a transition of the ion ensemble to a fluidlike state when cooled to temperatures below approximately 14 K. With the final ion temperature presently being 7.5 K, ions of the highest charge states are expected to form ion crystals by mere resistive cooling, in particular not requiring the use of laser cooling.
Gesehen am 12.07.2019